STUDENTS’ PERCEPTION OF ONLINE LEARNING USING WHATSAPP DURING COVID-19 PANDEMIC - Firda; Nur Asmawati; Afifah (English Tadris Department, Faculty of Tarbiyah and Teacher Training, State Islamic University (UIN) Datokarama Palu, 2022)
The purpose of this study is to find out students' perceptions of online learning during the covid-19 pandemic by using WhatsApp. This research used quantitative descriptive research. The population of this research was 67 people, while the research sample used was simple random sampling based on the solving formula, so the sample in this study was 57 second semester of the English Tadris Department at UIN Datokarma Palu. The instrument used was a questionnaire. The results of the study indicate that online learning using the WhatsApp application has been going well or it can be interpreted that online learning during the pandemic using the WhatsApp application was very helpful. The percentage obtained in this study is; positive (4.38%), while the negative obtained (4.01%), and neutral (1.59%). Based on the percentages above, we can see that online learning using the WhatsApp application during the pandemic really helped students in the learning process even though they did not have face-to-face classes.